(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Ethnic tourism in Uzbekistan embraces one of the most fascinating types of travel, for what characterizes a land more vibrantly than its unique ethnic flavor? As you encounter a national heritage which has been developing for centuries, you will discover ancient traditions which are still prevalent in modern life.